2019
DOI: 10.1021/acs.langmuir.9b02217
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Mediated Affinity of Polymer-Wrapped Single-Walled Carbon Nanotubes for Chemically Modified Surfaces

Abstract: Semiconducting single-walled carbon nanotube (s-CNT) arrays are being explored for next-generation semiconductor electronics. Even with the multitude of alignment and spatially localized s-CNT deposition methods designed to control s-CNT deposition, fundamental understanding of the driving forces for s-CNT deposition is still lacking. The individual roles of the dispersant, solvent, target substrate composition, and the s-CNT itself are not completely understood because it is difficult to decouple deposition p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…An alternative and a powerful way to characterize the corona phase includes computational modeling approaches, such as classical molecular dynamics (MD) simulations, which enable atomic resolution on the timescale of hundreds of nanoseconds 1,2,[29][30][31][32] . Yet, as reorganization of long polymers on SWNT surfaces occurs on a timescale of several nanoseconds, determining most probable equilibrium distributions of polymers in the corona phase necessitates enhanced sampling approaches, such as temperature replica exchange (T-REMD) MD simulations 33 .…”
Section: Introductionmentioning
confidence: 99%
“…An alternative and a powerful way to characterize the corona phase includes computational modeling approaches, such as classical molecular dynamics (MD) simulations, which enable atomic resolution on the timescale of hundreds of nanoseconds 1,2,[29][30][31][32] . Yet, as reorganization of long polymers on SWNT surfaces occurs on a timescale of several nanoseconds, determining most probable equilibrium distributions of polymers in the corona phase necessitates enhanced sampling approaches, such as temperature replica exchange (T-REMD) MD simulations 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The polymer-wrapped s-CNTs prefer to adsorb on SiO 2 compared to octadecylsilane (OTS)-grafted silicon oxide due to solvent structure effects. 42 To take advantage of s-CNT adsorption preferences to drive selective-area deposition, alternating stripes of SiO 2 and OTS were patterned using an electron-beam lithography (EBL) process illustrated in Fig. 1a .…”
Section: Resultsmentioning
confidence: 99%
“…Recently through a systematic study, we reported that varying the substrate chemistry by using self-assembled monolayers (SAMs) impacts the number density of deposited s-CNTs from solution. 42 While substrate water contact angle alone was insufficient to explain the observed s-CNT adsorption trends on these chemically modified substrates, molecular dynamics (MD) simulations provided useful mechanistic insights. In particular, the solvent-mediated affinity of polymer-wrapped s-CNTs played a key role in s-CNT deposition onto a surface.…”
Section: Introductionmentioning
confidence: 99%
“…So far, various type of adsorbents are in use for the treatment of wastewater such as carbon nanotubes [8][9][10], graphenes and its derivatives [11], natural zeolites, and modified organic wastes [12]. Currently, the interest in using chemically modified organic wastes as adsorbents for the treatment of wastewater has increased due to their cost effectiveness and biodegradability.…”
Section: Introductionmentioning
confidence: 99%